2017
DOI: 10.1016/j.bone.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of klotho in human chronic kidney disease

Abstract: The extracellular domain of transmembrane alpha-Klotho (αKlotho, hereinafter simply called Klotho) is cleaved by secretases and released into the circulation as soluble Klotho. Soluble Klotho in the circulation starts to decline early in chronic kidney disease (CKD) stage 2 and urinary Klotho possibly even earlier in CKD stage 1. Therefore soluble Klotho could serve as an early and sensitive marker of kidney function decline. Moreover, preclinical animal data support Klotho deficiency is not just merely a biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
89
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 146 publications
2
89
1
2
Order By: Relevance
“…Consistent with these findings, we recently observed that s-Klotho inhibited endoplasmic reticulum stress-induced apoptosis in obstructive nephropathy7 and epithelial mesenchymal transition (EMT)-induced renal fibrosis in cyclosporin nephropathy 8. These results indicate that s-Klotho is involved in various kidney diseases, and it has been proposed as a novel renal protective protein with therapeutic potential 9. s-Klotho is located predominantly in the kidney, parathyroid gland, and choroid plexus.…”
Section: Introductionsupporting
confidence: 65%
“…Consistent with these findings, we recently observed that s-Klotho inhibited endoplasmic reticulum stress-induced apoptosis in obstructive nephropathy7 and epithelial mesenchymal transition (EMT)-induced renal fibrosis in cyclosporin nephropathy 8. These results indicate that s-Klotho is involved in various kidney diseases, and it has been proposed as a novel renal protective protein with therapeutic potential 9. s-Klotho is located predominantly in the kidney, parathyroid gland, and choroid plexus.…”
Section: Introductionsupporting
confidence: 65%
“…25 The ectodomain of membrane-anchored αKlotho is shed by secretases [26][27][28] into the circulation, and exerts FGF23-independent actions including antiaging, antiapoptosis, anti-senescence, and blockade of vascular calcification. 29,30 Soluble αKlotho, a cleaved extracellular domain of membrane-anchored αKlotho protein was proposed to also function as a deliverable soluble receptor for FGF23 in very high concentrations in vitro. 31 The cellular and molecular mechanisms by which αKlotho deficiency initiates and/or promotes aging are not understood.…”
Section: Introductionmentioning
confidence: 99%
“…While this has been enormously useful as proofof-concept in experimental animals, this technique is not applicable to patients currently. Recombinant Klotho protein was used successfully in the laboratory in both acute and chronic [5] settings that prevented AKI, accelerated AKI recovery, presented and retarded AKI-to-CKD transition, and ameliorated extrarenal complications [4]. Recombinant Klotho protein administration is a method where translation to human therapeutics is much more practical and proximal.…”
mentioning
confidence: 99%
“…In multiple preclinical studies with diverse models, both acute and chronic kidney diseases are states of renal and systemic klotho deficiency [3], including human CKD. The relationship between Klotho and kidney disease is more than just a biomarker because restoration of Klotho ameliorated renal dysfunction and extrarenal complications in both acute [4] and chronic settings bringing Klotho supplementation into the therapeutic realm. However, how should Klotho be given?…”
mentioning
confidence: 99%
See 1 more Smart Citation